Risk Management of Granola Potato Seeds Production: A Study in Kertasari, West Java, Indonesia - Eliana Wulandari; Ernah Ernah; Hepi Hapsari; Amelia Hendra (Caraka Tani: Journal of Sustainable Agriculture, 2021)
The quality of potato seeds is important to support increased production. The majority of farmers do not certify potato seeds, which can result in various risks for potato seed production activities. This research aims to identify the risks of potato seed production and formulate risk control strategies for potato seeds production. The research uses house of risk method. The results of this study show thirty-nine identified risk events. The most impactful risk event was rotten potato. Thirty-two identified risk agents with two priorities must be handled first. The most effective ways in handling strategy are training, the certification of potato seed breeder farmers, potato seed certification, as well as purchasing breeder seeds from vegetable crop research center and from other seed breeders. This research suggests the needs to produce quality potato seeds by certifying potato seed and to update the competency certification of potato seed breeders.